2010
DOI: 10.1007/s00428-010-0982-9
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin embryopathy: fetal manifestations

Abstract: During the period 1991-2007, autopsy was undertaken in 13 fetuses with warfarin embryopathy. Pregnancy data and radiographic babygrams were available in each instance. Gestational age ranged from 17 to 37 weeks. Eleven of the fetuses had the characteristic nasal hypoplasia, but only three had radiological epiphyseal stippling. Cerebral hemorrhage was a major feature of autopsy in 8 of the fetuses, and it is evident that bleeding is a significant factor in the pathogenesis of warfarin embryopathy. A wide variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…The most consistent fetal anomalies described are nasal hypoplasia, depressed nasal bridge, stippling of uncalcified epiphyses (most frequently affecting the axial skeleton, proximal femur and calcaneus), mild hypoplasia of the nails and shortened fingers. Franco et al 12 suggested that warfarin may inhibit arylsulfatase enzyme activity, the cause of X-linked recessive chondrodysplasia punctata which is phenotypically similar to warfarin embryopathy 4. Although warfarin seems to be the safest anticoagulation for pregnant women with mechanical heart valves, this treatment is associated with the risk of congenital malformations in the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent fetal anomalies described are nasal hypoplasia, depressed nasal bridge, stippling of uncalcified epiphyses (most frequently affecting the axial skeleton, proximal femur and calcaneus), mild hypoplasia of the nails and shortened fingers. Franco et al 12 suggested that warfarin may inhibit arylsulfatase enzyme activity, the cause of X-linked recessive chondrodysplasia punctata which is phenotypically similar to warfarin embryopathy 4. Although warfarin seems to be the safest anticoagulation for pregnant women with mechanical heart valves, this treatment is associated with the risk of congenital malformations in the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the abnormalities seen in Keutel syndrome are also common in chondrodysplasia punctata and warfarin embryopathy (Franco et al., ; Munroe et al., ; Wainwright & Beighton, ). Although it is known that the inactivation of arylsulfatase E (ARSE) leads to chondrodysplasia punctata, the actual substrate and function of this enzyme are still unknown (Weaver et al., ).…”
Section: Midface Hypoplasia Caused By Abnormal Cartilage Calcificatiomentioning
confidence: 99%
“…Similar features are seen in warfarin embryopathy (Fryns, van Fleteren, Mattelaer, & van den Berghe, 1984;Munroe et al, 1999) Warfarin embryopathy -Seen in children born to mothers treated with warfarin, an anticoagulant. Developmental abnormalities are similar to chondrodysplasia punctata and Keutel syndrome (Starling, Sinha, Boyd, & Furck, 2012;Wainwright & Beighton, 2010) (Franco et al, 1995;Munroe et al, 1999;Wainwright & Beighton, 2010). Although it is known that the inactivation of arylsulfatase E (ARSE) leads to chondrodysplasia punctata, the actual substrate and function of this enzyme are still unknown (Weaver et al, 2014).…”
Section: Keutel Syndrome Autosomal Recessive; Mgpmentioning
confidence: 99%
“…3,12,13,16 Supporting these observations, offspring of pregnant women receiving warfarin showed shortening and flattening of the nose, epiphyseal stippling, and cerebral hemorrhage. 31 Warfarin inhibits the VKORC1 complex, which recycles vitamin K. Offspring of pregnant rats treated with warfarin showed calcification and disruption of hypertrophic chondrocytes in long-bone epiphyses. These studies indicate that early gestational warfarin exposure results in bone dysplasia, whereas later exposure affects coagulation factors.…”
Section: Etiologies For Bcp In Patients Without Arse Mutationsmentioning
confidence: 99%